Simulation of slope stability with Eugenia Oleina against soil erosion - Nor Farzana, Abdul Haris (2019)
Soil bioengineering techniques has been used worldwide as to control the slope stability. A commonly used idea is to apply live pole at the slope area in order to prevent the soil erosion which causing the problem in geotechnical engineering. Soil erosion may occur due to heavy rainfall or also from soil matrix pressure. This research is conducted with aim to find out the cause of soil erosion that occured at the slope near FKASA surveying lab in University Malaysia Pahang and the purpose of having Eugenia Oleina species planted on the slope whether it is helpful in preventing soil erosion. In this research, the results from the previous lab test was used in simulating the slope stability with Eugenia Oleina using the finite element software that is widely used in geotechnical engineering, which is known as Plaxis 2D. The factor of safety obtained from the simulation shows that the rooted soil with Eugenia Oleina are low compared to the unrooted soil.